HUBUNGAN AKTIVITAS SPIRITUAL DENGAN TERJADINYA PENURUNAN FUNGSI KOGNITIF PADA LANSIA - Na'imah, Ana Ainun; Yazid, Noor; Fuad, Wijayanti (Universitas Tadulako, 2024)
The decreased cognitive function indicates a decreased brain function which can affect independence. This disorder often impacts social life, psychology, and physical activity in the elderly. It is estimated that up to a third of adults will experience a gradual decreased cognitive function. The decreased cognitive function can be prevented by maximizing the working power of the brain, one of which is through spiritual activity. This study aims to determine the relationship between spiritual activity and the level of cognitive function decline in the elderly. This study used a cross-sectional design method with data from the spiritual activity questionnaire and the Mini Mental State Examination (MMSE) with 23 respondents. The sample selection was done by purposive sampling, with data analysis using the chi-square test. The results of the study showed that p-value < 0.05 meant that there was a relationship between spiritual activity and cognitive function in the elderly. This study shows a significant relationship between spiritual activity and decreased cognitive function in the elderly. Most of the elderly who regularly carry out spiritual activities have a good cognitive function. Therefore, to minimize the decline in cognitive function in the elderly, it is necessary to carry out regular spiritual activities.